"Sucrose analgesia": absorptive mechanism or taste perception?. Issue 2 (1st March 1999) - Ramenghi, Luca A; Evans, David J; Levene, Malcolm I
Abstract : It remains unclear whether "sucrose analgesia" is related to a pre- or postabsorptive mechanism. In a double blind cross over study sucrose reduced the pain response of preterm infants exposed to heel prick blood samples only when it was administered into the mouth. It was ineffective when administered intragastrically.